Catalogue drawing: A framing device for design thinking - Afifah Karimah; Paramita Atmodiwirjo (ARSNET, 2021)
This paper discusses the role of catalogue drawing as a framing device to aid design thinking in the architectural design process. Catalogue drawing has been largely understood as a representation of the finished and curated design output. However, it is argued that catalogue drawing enables designers to handle, arrange, and process information, assisting them to frame this information for different needs of design discovery. This paper analyses the catalogue drawings produced by first-year Bachelor of Architecture Programme students in Universitas Indonesia in doing their first creative making project. The study highlights four categories of catalogue drawings with various roles, from catalogue drawing intended to capture the relevant information, investigate the particularities, create a bigger picture of the design condition, and outline the design proposition. The study found that each catalogue drawings were often repeated in loops throughout the design process, enabling the students to incrementally generate original design works. This study underlines the role of catalogue drawing in revealing the progression of design thinking that is often hidden throughout the architectural design process.